THE SUPERNATURAL AS LANGUAGE GAME - Klein, Terrance W. (Zygon, 2006)
For many in the Anglo‐American tradition of language analysis, Ludwig Wittgenstein, the great progenitor of twentieth‐century philosophy of language, showed conclusively that theological terms lack any referent in reality and therefore represent a discourse that can do no more than manifest the existential attitudes that speakers take toward reality as a whole. To think that such terms represent more is to be bewitched by the use of language. Is it possible, however, that theological language references a fundamental human drive? In this article I reexamine the dyad of nature and supernature from the perspective of Wittgenstein's philosophy. Perhaps surprisingly, Wittgenstein's thought on the subject offers much more than his famous, terse aphorism at the conclusion of his first masterwork, the Tractatus Logico‐Philosophicus ([1921] 1961, 74, §7): “What we cannot speak about we must pass over in silence.” Furthermore, the basic Tractarian drive to determine the relationship between language and reality, which is redirected but not extinguished in Wittgenstein's second, divergent, opus, the Philosophical Investigations ([1953] 1967), may be the place for a renewed examination of what the supernatural means in human discourse. Does talk of God give expression to the fundamental transcendence of human knowledge? Is it a language game we can eschew?